ESG performance and dividend policy: The moderating role of family ownership in Indonesia - Prahbawati, Ni Komang Wahyu Trisna; Isnalita, Isnalita (Jurnal Akuntansi dan Auditing Indonesia, 2025)
This study examines the effect of ESG performance on dividend policy and analyzes the moderating role of family ownership in Indonesian non-financial firms. Using a quantitative approach, multiple linear and moderated regression analyses were conducted on data from 208 firms listed on the IDX between 2019 and 2023, sourced from OSIRIS, Bloomberg, and company reports through purposive sampling. The findings show that ESG performance positively and significantly affects dividend policy, supporting stakeholder theory that emphasizes corporate responsibility and long-term stability. However, family ownership weakens this positive relationship, aligning with agency theory’s Type II conflict between controlling and minority shareholders. These results suggest that regulators, investors, and managers should consider ownership structure when developing dividend and sustainability policies. This study contributes novel empirical evidence by integrating ESG performance, dividend policy, and family ownership within a single framework in Indonesia’s emerging market, where family control remains prevalent.